PENGARUH KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN DI PERUSAHAAN JMS BATAM - Anisa Rifqi Aulia; Ageng Rara Cindoswari (SCIENTIA JOURNAL, 2025)
The success of a business that produces medical devices heavily depends on employee performance, especially considering the increasing demand and strict quality requirements. This research examines how much of an impact organizational communication on employee performance at JMS Batam Company, a Japanese multinational operating in the medical equipment sector. According to organizational communication theory, particularly network theory, good communication within an organization creates a network of interpersonal relationships that accelerates decision-making, enhances collaboration, and improves performance. For this quantitative study with an explanatory design, 96 respondents were selected using a simple random selection process. the extent to which data was collected via semi-structured interviews and questionnaires, and how descriptive statistics and basic linear regression were employed for analysis. With a t value of 4.200 above the t tabel value of 1.985 and 0.000 as the significance threshold, the study's results demonstrate that organisational communication significantly and favourably affects employee performance. These findings indicate that improving company communication can significantly enhance employee performance. This study provides recommendations to enhance employee support, feedback, and communication flow to improve employee well-being and productivity within the company